Biomimetic Microfluidic Platforms for the Assessment of Breast Cancer Metastasis - Sigdel, Indira; Gupta, Niraj; Faizee, Fairuz; Khare, Vishwa M.; Tiwari, Amit K.; Tang, Yuan (Frontiers in Bioengineering and Biotechnology, 2021)
Of around half a million women dying of breast cancer each year, more than 90% die due to metastasis. Models necessary to understand metastatic process, particularly breast cancer cell extravasation and colonization, are currently limited and are urgently needed to develop therapeutic interventions necessary for the prevention of breast cancer metastasis. Microfluidic approaches aim to reconstitute functional units of organs that cannot be modeled easily in traditional cell culture or animal studies by reproducing vascular networks and parenchyma on a chip in a three-dimensional, physiologically relevant in vitro system. In recent years, microfluidics models utilizing innovative biomaterials and microengineering technologies have shown a great potential in our effort of mechanistic understanding of breast cancer metastasis cascade by providing 3D constructs that can mimic in vivo cellular microenvironment and the ability to visualize and monitor cellular interactions in real-time. In this review, we will provide readers with a detailed discussion on the application of the most up-to date, state-of-the-art microfluidics-based breast cancer models, with a special focus on their application in the engineering approaches to recapitulate the metastasis process, including invasion, intravasation, extravasation, breast cancer metastasis organotropism and metastasis niche formation.